Microneedles integrated with a triboelectric nanogenerator: an electrically active drug delivery system. Issue 28 (4th July 2018) - Bok, Moonjeong; Lee, Yunwoo; Park, Daehoon; Shin, Sangho; Zhao, Zhi-Jun; Hwang, Boyeon; Hwang, Soon Hyoung; Jeon, So Hee; Jung, Joo-Yun; Park, Sung Ha; Nah, Junghyo; Lim, Eunju; et al.
Abstract : A combined system of microneedles and a triboelectric nanogenerator (TENG) was designed and utilized as a portable electrically active drug delivery device. Abstract : In this study, a combined system of microneedles and a triboelectric nanogenerator (TENG) has been developed for drug delivery. A triboelectric device, which converts mechanical energy into alternating current (AC), was chosen to replace the electrophoresis (EP) effect. To directly generate triboelectricity from salmon deoxyribonucleic acid (SDNA)-based microneedles, a triboelectric series of SDNA film and chargeable polymers (polyimide and Teflon) was studied. The electrical output of the two charged polymers was compared to find a material that could be highly charged with SDNA. The electrical output was also compared as a function of the concentration of a drug embedded in the SDNA film, and the results confirmed that drug intercalation affected the carrier diffusion. The mechanical strength of the microneedles was assessed by histological analysis of their penetration into porcine cadaver skin. Furthermore, the output voltage of a system incorporating microneedles and TENG in cadaver skin, and in vitro drug release into gelatin were evaluated to examine potential application as an electrically active drug delivery system. The electrical output voltage of this system was ∼95 V. The mechanism of triboelectric perturbation to the skin has also been discussed. The system developed in this work is a new, facile approach toward effective drug delivery that replaces the existing EP method and expands the application of TENGs.